Association between universal hepatitis B prison vaccination, vaccine uptake and hepatitis B infection among people who inject drugs. (21st August 2017) - Palmateer, Norah E.; Goldberg, David J.; Munro, Alison; Taylor, Avril; Yeung, Alan; Wallace, Lesley A.; Mitchell, Alan; Shepherd, Samantha J.; Gunson, Rory N.; Aitken, Celia; Hutchinson, Sharon J.
Abstract: Background and aims: In Scotland, hepatitis B virus (HBV) vaccination for all prisoners was introduced in 1999; here, we examine the impact of this programme among people who inject drugs (PWID) in the community. This study aimed to compare rates of HBV vaccine uptake before and after implementation of the prison programme and to estimate the determinants of vaccine uptake, the levels of ever/current HBV infection and the associations between vaccine uptake and ever/current HBV infection. Design: Data collected via serial cross‐sectional surveys were used to compare the proportion who reported being vaccinated over time. For the 2013–14 survey, rates of ever/current HBV infection were calculated and the associations between vaccine uptake and ever/current HBV infection were examined using logistic regression. Setting: Services providing injecting equipment and drug treatment and street sites in Glasgow (1993–2002) and throughout Scotland (2008–14). Participants: More than 10 000 PWID in total were recruited in the surveys. Measurements: Participants completed a questionnaire (all years) to ascertain self‐reported vaccine uptake and provided a blood spot (in 2013–14), tested for HBV core antibodies (anti‐HBc) and surface antigen (HBsAg). Findings: Among recent‐onset PWID in Glasgow, vaccine uptake increased from 16% in 1993 to 59% in 2008–14 ( P  < 0.001). Among all PWID in Scotland, uptake increased further from 71% in 2008–09 to 77% in 2013–14 ( P  < 0.001) and was associated with incarceration [adjusted odds ratio (aOR) = 2.91, 95% confidence interval (CI) = 2.23–3.79]. The prevalence of anti‐HBc and HBsAg in Scotland was 2.6 and 0.3%, respectively, among PWID who had commenced injecting in the decade since the programme's introduction. Vaccination was associated with reduced odds of ever (aOR = 0.60, CI = 0.37–0.97) and current (aOR = 0.40, CI = 0.16–0.97) HBV infection. Conclusions: In Scotland, uptake of hepatitis B virus (HBV) vaccination among people who inject drugs (PWID) in the community has increased since the 1999 introduction of universal prison vaccination, and current levels of HBV infection among PWID are low compared with other European countries.